EVALUATION OF RESULTS OF THE FIRST EXPERIENCE OF COMBINED SURGERY FOR VARICOSE VEINS AND KNEE OSTEOARTHRITIS - O. NEMATZODA; A.D. GAIBOV; O.F. SOLIEV; KH.A. TOSHPULOTOV; S.G. ALI-ZADE; A.K. BARATOV (Паёми Сино, 2022)
Objective: To analyze the results of the first experience of performing simultaneous operations for saphenous varicose veins of the lower extremities and knee osteoarthritis.